Comparing quality of aerial photogrammetry and 3D laser scanning methods for creating 3D models of objects - Daugėla, Ignas; Sužiedelytė-Visockienė, Jūratė; Stanionis, Arminas; Tumelienė, Eglė; Antanavičiūtė, Urtė; Aksamitauskas, Vladislovas Česlovas (International Conference “Environmental Engineering”, 2017)
Latest technologies are modern and productive, therefore they are increasingly becoming integral part of any engineering work. Information about real-world objects are collected very quickly and accurately using either spatial data of a terrestrial 3D laser scanners or photographic material obtained from unmanned aircraft vehicle (UAV). After processing data with special software three-dimensional spatial data of objects are obtained, which use is extensive. These data are needed for building facades measurements and inventory, construction, environmental studies, mining, archeology, civil engineering works and for building infrastructure modeling (BIM) systems that are currently being integrated in Lithuania. The result should ensure a high level of accuracy and quality. The article examines 3D modeling using different methods of the selected object. Systems characteristics, quality analysis of 3D models, recommendations and conclusions has been made.
Keywords: laser scanning; 3D modelling; unmanned aerial vehicle; photogrammetry